Composite sandwich panels subjected to quasi-static bending loads - Lim, Jin Han. (2012)
Circular composite sandwich panels consisting of Glass Fiber Reinforced Plastic (GFRP) face sheets and Divinycell H35 grade PVC foam cores are quasi-statically loaded with a flat-ended circular punch to investigate the dominant plastic collapse modes. Quasi-isotropic laminates employed for the face sheets give an axisymmetric response under the central punch loading condition. 4 competing failure modes: indentation, core shear, face sheet punching and face sheet micro-buckling have been identified, of which the micro-buckling failure mode is not obtainable due to the low density of the H35 foam core. Active failure mechanism is dependent upon the design geometry of the sandwich plates, specifically varied in terms of face-sheet-to-core thickness ratios (t/c) and core thickness to plate radius (c/R) ratios. Ratio of plate to punch radius (R/a) and core to face sheet yield strength (σcY/σfY) is thus kept constant for better predictability of results and trend. Load versus extension response was obtained for each of the loading tests for the analysis of the failure mechanism. Subsequent comparisons of finite element simulation results and analytical predictions of failure loads and stiffness generally show good agreement with the measured responses.